DEM modelling analysis of tree root growth in street pavements. Issue Volume 18:Issued 1(2017) (2nd January 2017) - Giuliani, Felice; Autelitano, Federico; Degiovanni, Elisa; Montepara, Antonio
Abstract : The coexistence of urban green spaces and infrastructure is often difficult. Trees find inhospitable environments in urban areas, whereas tree root systems can damage sidewalk, street and parking lot. The main form of failure concerns the growing of tree roots beneath the pavements, which produce upheavals and displacements on wearing course. The main objective of this study was a distinct element method modelling analysis of the potential interactions between tree root systems and street pavements. This calculation code allowed us to simulate the dynamic behaviour of the ground-pavement system as result of the roots growth. The performed modelling, representative of various planting strategies commonly used in urban contexts, have highlighted the progressive reduction of deformations with the increase of the roots penetration depth. Such displacements were strongly influenced by other factors such as the porosity and the grain-size distribution of the soil and the type of pavement considered.